Вікідидактика − складник новітньої медіадидактики в соціальній мережі Фейсбук - Білецький, Володимир Стефанович; Онкович, Ганна Володимирівна; Онкович, Артем Дмитрович (RS Global Sp. z O.O., Poland, 2021)
The article deals with a new pedagogical branch of "wikididactics" and its presentation on Facebook. Wikididactics is considered as a part of pedagogy, which deals with the use of Wikipedia in the educational process, development and testing of new didactic materials based on Wikipedia sources. Terminological base of the direction "Wikididactics" today includes the following concepts: wiki user, wikimedian, wikipedian, wiki educator, wikididact. Wikididactics is the newest branch of modern media didactics, presented on the social network Facebook. The materials of the Facebook page are aimed at developing the media educational and socio-cultural competencies of its users. The results of the content analysis of the FB page "Wikididactics" are offered.
Keywords: media education; high school media didactics; wikididactics; wiki lesson; Internet resource; social network